STUDENT SERVICES INFORMATION SYSTEM IMPLEMENTATION CASE STUDY: THE STUDY PLAN CARD ON-LINE IN JAKARTA STMIK STI & K - Irfan Irfan Irfan (Majalah SIKOMTEK, 2004)
The success of a college that can not be separated from palayanan given to students inparticular about the manner of taking courses that will be given in each semester. KRSmakingsystem on line this will greatly help the student in completing his studies and tofacilitate in determining the number of active students.